Assessment of enzymatically synthesized DNA for gene assembly - Simmons, Brooke L.; McDonald, Nathan D.; Robinett, Natalie G. (Frontiers in Bioengineering and Biotechnology, 2023)
Phosphoramidite chemical DNA synthesis technology is utilized for creating de novo ssDNA building blocks and is used widely by commercial vendors. Recent advances in enzymatic DNA synthesis (EDS), including engineered enzymes and reversibly terminated nucleotides, bring EDS technology into competition with traditional chemical methods. In this short study we evaluate oligos produced using a benchtop EDS instrument alongside chemically produced commercial oligonucleotides to assemble a synthetic gene encoding Green Fluorescent Protein (GFP). While enzymatic synthesis produced lower concentrations of individual oligonucleotides, these were available in half the time of commercially produced oligonucleotides and were sufficient to assemble functional GFP sequences without producing hazardous organic chemical waste.